Vão-se os anéis, ficam os dedos: reconfiguração da elite empresarial brasileira pós financeirização econômica - Julian, Erica Ambiel (Universidade Federal de São Carlos, 2018)
In Brazil, the elite helped building policies. In order to get benefits for different sectors, the agents seek ways to get some power spaces, integrating influence spaces or occupying some strategic positions and chairs, such as councils, elected offices and class representation. This construction of specific policies for certain sectors is done with the direct or indirect help from the opinion of their most outstanding representatives. Understanding how elite influence the government actions is important to project the influence of the elite in the state political formation. In relation to the economic elite, it is possible to verify this assertion by observing the relation between the business people and the political groups. The entrepreneurs become relevant agents upon the national political thought, boosting the country’s directions, advising the governments that focus on development, creating discourses on behalf of economic interests. By analysing how they act in the political scenario, it is possible to perceive that the action is adapted to the context, distinguishing the ways of operating the relations between political and economic spaces according to the temporary cut. Therefore, it is possible to see that, almost in an instinctive form, the economic elite, or business people, use different entries to the political environment to defend their interests. In this work, we will explore how the economic elite have access to the political elite or to the entries to the political field. Gerdau is a one-hundred-year familiar company that, after the financialization of its operations and a bigger internationalization, has suffered organizational changes that have resulted in a significantly changing in its management staff. Gerdau has one of the most recognized representatives of the corporate class in the country, Jorge Gerdau Johannpeter, who takes part in the organization evolution and has already been director and president and, currently, is an advisor to the Group. In observing his biography, it is possible to understand that the agent's form of action, coming from the economic elite that transfers capital to the political field, is modified according to the institutional changes that politics imposes on the nation state. This conclusion was obtained after the data collection, found through the media collection made available by the Brazilian Digital Library (Hemeroteca Digital Brasileira da FundaçãoBiblioteca Nacional) and other sources.

Au Brésil, le champ des élites a aidé à construire des politiques publiques. Afin de recevoir des avantages pour différents secteurs de l’économie, les agents cherchent des moyens d'entrer dans des espaces de pouvoir, d'intégrer des espaces d'influence ou d'occuper des positions stratégiques, tels que des conseils, des élus et une représentation de classe. La construction de politiques spécifiques pour certains secteurs se fait avec l'aide directe ou indirecte des opinions de leurs représentants qui ressortent davantage. Comprendre comment l'influence des élites se produit dans les actions gouvernementales est important pour projeter l'influence des élites dans la formation politique de l'État. En ce qui concerne l'élite économique, cette affirmation peut être validée par l’observation des relations entre les entrepreneurs et les groupes politiques nationaux. Les entrepreneurs sont devenus et des agents pertinents dans la pensée politique nationale, aident à penser les orientations du pays, recommandent des actions aux gouvernements, dans la création des discours au nom des intérêts économiques. L’analyse temporel fait voir la façon comment ils agissent dans le scénario politique, c’est possible de percevoir que l'action s'adapte au contexte, distingue les manières d'opérer les relations entre l'espace politique et économique en fonction de la coupure temporelle. Ainsi, il s'avère que, presque instinctivement, les élites économiques, ou les entrepreneurs, utilisent différentes entrées dans l'environnement politique pour défendre leurs intérêts. Nous explorons ici la manière que les élites économiques peuvent accéder aux élites politiques ou entrér dans l'arène politique. Gerdau est une entreprise familiale centenaire qui, après la financiarisation de ses opérations et l'internationalisation croissante, a subi des changements organisationnels qui ont entraîné une transformation importante de son équipe de direction. Gerdau a l'un des représentants les plus reconnus de la classe d'entreprise dans le pays, Jorge Gerdau Johannpeter, qui participe à l'évolution de l'organisation et etait directeur, président et maintenant conseiller du Groupe. Au regarde de sa biographie, il est possible de comprendre que la forme d'action de l'agent, issue de l'élite économique qui transfère le capital vers le champ politique, est modifiée suite aux changements institutionnels que la politique impose à l'État national. Cette conclusion a été obtenue après la collecte de données, grâce à la collection de médias mis à disposition par la Biblioteca Nacional et d'autres sources.
Seront perdus les anneaux, rester des doigts: reconversion du capital et la restructuration des élites économique brésilienne après financiarisation économique
The rings are going: reconfiguration of the Brazilian business elite after economic financialization
Keywords: Sociologia econômica; Empresários; Grupo Gerdau; Economic sociology; Entrepreneurs; Gerdau group; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS